PENERAPAN MODEL PEMBELAJARAN BERBASIS INKUIRI UNTUK MEMBERDAYAKAN KETERAMPILAN KERJA ILMIAH DAN PEMAHAMAN KONSEP MAHASISWA - Hadi, Lukman (Jurnal Pendidikan Matematika dan IPA, 2016)
The aim of this study was to describe conceptual understanding and sciences process skills of students through inquiry-based learning. The study was conducted in form of one group pretest-posttest design. Thirty five students of chemistry education program of fkip untan participated. Result showed difference of sciences process skills and conceptual understanding of students, before and after inquiry based-learning. Sciences process skills of students improved from 0% to 52% and 16% to 40% on very skilled and skilled categories respectively. Furthermore, conceptual understanding of students improved from 15% to 89%. To conclude, inquiry-based learning was able to improve conceptual understanding and sciences process skills of students. Key words: Inquiry-based learning, conceptual understanding, sciences process skills.